2018
DOI: 10.1111/aman.13050
|View full text |Cite
|
Sign up to set email alerts
|

Time and Relational Possibility: Cultural Anthropology in 2017

Abstract: This essay reviews work produced in predominantly US cultural anthropology publications throughout 2017. It asks: What makes an anthropological inquiry timely, what sorts of relationalities command anthropological attention, and to what end? Noting our ongoing methodological commitment to long-term ethnography alongside increasingly important online forums for reaching broader publics and responding quickly to emerging issues, it expands the range of work surveyed to include some online-only short essays along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 279 publications
(290 reference statements)
1
2
0
Order By: Relevance
“…Through captivity and its unruly failures, cultural anthropologists recast familiar concerns about structure and agency for the present, drawing our attention to new ethnographic sites and ways of thinking about governance, temporality, scale, affect, political economy, posthumanism, ontology, care, and infrastructure. These emphases remain relatively consistent with recent years, as Tamarkin () last year suggested that temporality (mobility and sovereignty) and relationality (subjectivity and mediation) were our key foci.…”
Section: On Staying With the Troubles Of Carceralitysupporting
confidence: 73%
See 1 more Smart Citation
“…Through captivity and its unruly failures, cultural anthropologists recast familiar concerns about structure and agency for the present, drawing our attention to new ethnographic sites and ways of thinking about governance, temporality, scale, affect, political economy, posthumanism, ontology, care, and infrastructure. These emphases remain relatively consistent with recent years, as Tamarkin () last year suggested that temporality (mobility and sovereignty) and relationality (subjectivity and mediation) were our key foci.…”
Section: On Staying With the Troubles Of Carceralitysupporting
confidence: 73%
“…In recent years, cultural anthropologists have focused on what Ortner () identified as “dark anthropology” and “anthropologies of the good.” Waterston's () Presidential Address at the American Anthropological Association meetings closed out 2017 by providing both a “lament” and an “affirmation,” grappling with the ways that cultural anthropologists seemed foundationally engaged in both acknowledging the “dark times” and “envisioning an alternative world” (Waterston , 258). Noah Tamarkin (, 306) characterized cultural anthropology in 2017 in last year's American Anthropologist year in review as grappling with darkness while also imagining better futures. In the year 2018—which was dominated by exclusionary nationalism manifest in Trump's border wall and Bolsonaro's victory in Brazil, economic and environmental uncertainty produced by debates over Brexit, trade wars, and increasingly apocalyptic projections of climate change, and continued US military involvement abroad alongside mass shootings at home—American cultural anthropology seemed to focus again on both darkness and hope, with particular attention to people's efforts at transformation.…”
mentioning
confidence: 99%
“…Nonetheless, they also establish value as a quantifiable relation wherein time acts as a common denominator. However, this book will not delve into the nearly limitless prospects of time's relational possibilities (Tamarkin 2018). Instead, I focus on clock-scaled resource time with the aim of providing a simple conceptual model of time as an equivalent that allows different kinds of value estimations to take place.…”
Section: Time and The Value Relationmentioning
confidence: 99%
“…University of Iowa emily-wentzell@uiowa.edu Anthropologists have long investigated how people's experiences of time reflect ongoing relationships between individual and group-level experiences. These experiences include people's understandings of the relationships between themselves and their societies in light of shared ideas about groups' origins, pasts, and desired futures (Munn 1992;Tamarkin 2018). Such studies have been particularly useful for understanding how cultural expectations for change over time relate to ideals and experiences of gendered personhood.…”
Section: Emily Wentzellmentioning
confidence: 99%